Sustainable Gift Packaging Design Based on KANO-AHP-QFD - Jiajia Fan; Wei Wang (BioResources)
As global environmental problems become increasingly severe and consumers' environmental awareness grows, traditional gift packaging is facing heavy criticism due to its excessive luxury orientation, high material consumption, and recycling difficulties. To address these challenges, this study proposed an innovative sustainable gift-packaging design methodology driven by user requirements and integrating the KANO model, Analytic Hierarchy Process (AHP), and Quality Function Deployment (QFD), aiming to enhance consumers’ willingness to adopt green practices and improve overall user experience. First, the KANO model was employed to identify and classify consumers’ packaging requirements, resulting in twenty user needs categorized by attribute. Second, AHP was used to construct a judgment matrix and calculate the composite weight of each requirement, thereby establishing the prioritization of design elements. Finally, QFD translated these user requirements into concrete design parameters, which were then ranked according to their importance. The resulting sustainable gift-packaging solution not only met users’ functional and aesthetic demands but also significantly elevated their environmental awareness. This research offers a scientifically grounded and practically applicable reference for the sustainable development of the packaging industry, while pointing to future research directions and potential applications in sustainable packaging design.